FISH YIELD FROM ASSAM PONDS KEPT UNDER DIFFERENT EXPERIMENTAL CONDITIONS - Parameswaran, S; Radhakrishnan, S; Selvaraj, C; Bhuyan, B R (Indian Journal of Fisheries, 2011)
Experiments conducted in ponds in Sibsagar, Assam, indicated that by liming,fertilization and artificial feeding, over six times the natural production of fish can profitablybe obtained.Fertilization of limed ponds with cow dung and N-P-K was found to be moreeconomical than fertilization of feeding with mustard oil-cake. A combination ofCatla catla, Labeo rohita and Cirrhinus mrigala gave better yields when oil-cake wasapplied as fertilizer whilst C. catla, L. rohita and Cyprinus carpio var. communis combinationyielded better when the same was given as alternate day feed. Catla showed themaximum growth potential among all the four species of carps. Scale carp grew fasterthan mrigal under comparable conditions. Unlike that of scale carp, the growth rateof catla, rohu and mrigal retarded during the winter months.